2017
DOI: 10.1002/bmb.21102
|View full text |Cite
|
Sign up to set email alerts
|

Small laccase from streptomyces coelicolor—an ideal model protein/enzyme for undergraduate laboratory experience

Abstract: A one semester undergraduate biochemistry laboratory experience is described for an understanding of recombinant technology from gene cloning to protein characterization. An integrated experimental design includes three sequential modules: molecular cloning, protein expression and purification, and protein analysis and characterization. Students perform the tasks of cloning, expression, purification, analysis, and characterization of small laccase (SLAC) from Streptomyces coelicolor. SLAC is an extremely robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…The experimental data showed that laccases from Streptomyces are oligomeric in nature [76]. The small laccase (SLAC) from S. coelicolor has been used as an ideal model system in laboratories for protein engineering [77]. Furthermore, the sequence analysis of SLAC laccases showed the trimeric protein of 114 and 98 kDa reported from S. griseus and S. sviceus, respectively [44,72].…”
Section: Laccase Activity Genomic Distribution and Structural Properties In Streptomycesmentioning
confidence: 99%
“…The experimental data showed that laccases from Streptomyces are oligomeric in nature [76]. The small laccase (SLAC) from S. coelicolor has been used as an ideal model system in laboratories for protein engineering [77]. Furthermore, the sequence analysis of SLAC laccases showed the trimeric protein of 114 and 98 kDa reported from S. griseus and S. sviceus, respectively [44,72].…”
Section: Laccase Activity Genomic Distribution and Structural Properties In Streptomycesmentioning
confidence: 99%
“…126 A pretest/post-test design applied to a course that incorporated inquiry-based learning activities within the context of PCR techniques found significant improvements in students' perceptions of their knowledge acquisition and their confidence in trouble-shooting and solving problems in the laboratory. 127 A laboratory setting that involved guiding students' learning using an inquiry-based teaching approach based on an instructor-created template that provided frequent feedback on students' work in a collaborative environment led to improvements in both students' satisfaction with the introductory biochemistry course and in the quality of the students' work. 128 Several studies have reported the benefits of providing students with 3D physical models of structures on the molecular scale 129 or a combination of 3D printed molecular models and molecular graphics software.…”
Section: ■ Laboratory Practicesmentioning
confidence: 99%
“…SLAC is characterized by resistance to reducing compounds and thermal stability. In addition, this enzyme exhibits the highest activity in the environment with pH 9 [11,50]. Owing to these features, SLAC have found their application in the pulp and paper industry for dye decolorization [11].…”
Section: Laccases Vs Others Mcosmentioning
confidence: 99%
“…SLAC charakteryzuje się opornoś cią na związki redukujące oraz stabilnością termiczną. Ponadto enzym ten wykazuje najwyższą aktywność w środowisku o pH 9 [11,50]. Dzięki tym cechom SLAC znalazły zastosowanie w przemyśle celulozowo--papierniczym do odbarwiania barwników [11].…”
Section: Lakazy Basidomycotaunclassified